Online media - Meadows-Klue, Danny (Henry Stewart Talks, 2009)
What are the steps in the process for advertising on the web?, The 10 step framework for online media plans, Researching consumer understanding, Applying consumer segmentation, Setting marketing objectives, Website selection for online media, Targeting techniques, Working well with your agency
Archived at 2022/04/11